Network analysis of an OSCE-based graduation skills assessment for clinical medical students - Huiqun Zhang; Shanshan Li; Guoquan Zheng; Xiaoyun Chen; Lujie Zhong; Jiaying Li; Yun Li (BMC Medical Education)
Abstract Background This study investigates OSCE performance among Chinese undergraduate medical students to identify differences and analyze the interconnections among OSCE modules. Employing network analysis, we map the relationships between modules to determine their predictive strength and centrality to overall clinical competence, offering a novel perspective on skill integration and curriculum design. Methods Analyzing data from 3,710 students across three medical specialities (clinical medicine, anesthesiology, medical imaging) from a leading medical institution in Guangzhou, China (Grade 2011–2016), and the independent samples t-tests, analysis of variance (ANOVA), Pearson’s correlation, and network analysis were employed to dissect performance trends, compare demographic group differences, and unearth the correlations among the examination modules. Results Significant differences were identified between genders, with female students consistently outperforming male students across modules and overall scores except for auxiliary examination analysis. Besides, specialities differed significantly in physical examination, basic operational skills, auxiliary examination analysis, and case analysis. Network analysis revealed that the nodes “Pediatric Skills” and “Nursing Skill” exhibit the strongest linkage, closely followed by “Cardiac Auscultation” and “Pulmonary Auscultation”. “General Physical Examination” is the most influential, with “Pediatric Skills” and “Gynecological Obstetrical Skills” also prominent. Conclusion From the perspective of medical education reform, reinforcing core skills like “General Physical Examination” and integrating modules to enhance skill synergy is pivotal. Implementing targeted educational interventions, including advanced training and clinical practice courses, will not only address performance disparities but also bolster students’ clinical acumen and communication skills, laying a robust foundation for superior patient care. The network analysis approach reveals how module performances interrelate, highlighting central modules whose improvement can boost related competencies. It complements traditional statistics, visualizing these relationships to inform OSCE reforms and enrich medical education.